Register Sundanese in the realm of Persib football - Nurulita, Dwi Hasna; Kadir, Puspa Mirani; Lyra , Hera Meganova (PT. Anagata Sembagi Education, 2025)
This research is motivated by the use of Sundanese language registers in the realm of football on the @Persib Instagram account. This study aims to determine the types and meanings of registers in the Persib Instagram account comments. This research method uses descriptive qualitative research methods with Sociolinguistic studies. The techniques used are observe and note. Based on the results of the analysis that has been done, 12 registers of Sundanese language in the realm of football were found on the Persib Instagram account. The research shows that the registers that appear are at the level of words and phrases, and can be classified into two types: open registers and closed registers. The results show that some registers such as jaga aci, mapay gawir, nyerepet jaer, megat paray, cegat muntah, and moe anduk have limited meanings derived from vocabulary that refers to nature, food, and daily life of Sundanese people. Some of them are formed through Sundanese morphemic processes such as affixation (nyetadion) and dwipurwa reduplication (pipinaltian). While open registers are registers whose meaning is relatively broad, but when used in the realm of football experience specification of meaning through changes in referents. Examples such as nyintir, cokel, eupan, and pancong, which in the context of the match experience meaning specifications without changing the basic form.